The Relationship Between Self Control and Sexual Behavior in SMK "X" Mojosari Students: Hubungan Antara Kontrol Diri dengan perilaku Seksual pada Siswa SMK "X" Mojosari - Nadia Eka Putri Sugiarto; Widyastuti (Academia Open, 2021)
The background in this study is the phenomenon of vocational students who are found to have problems with sexual behavior deviations, the purpose of this study is to determine the relationship between self-control and sexual behavior in vocational students. The variable included in this study is self-control as an independent variable and as a dependent variable for sexual behavior. This study was conducted in vocational training “X” Mojosari, with a sample of 84 students, using Probability Sampling, Proportional Strict Random Sampling. The data collection technique in this study uses the first two psychological scales of the Likert model, i.e., the thurstone scale for the self-control scale and the sexual behavior scale. The hypothesis in this study is that there is a relationship between self-control and sexual behavior in high school vocational training students. Data analysis was performed using the Pearson product moment correlation statistical technique using the Windows SPSS program. The results of the data analysis of this study indicate a correlation coefficient of 0.856 with a significance of 0.000 <0.05 means that there is a positively relationship between self-control and significant and unidirectional sexual behavior. So that the higher the self control, the more also high sexual behavior in students at vocational high school "X" Mojosari, as well otherwise. The contribution effective of self-control to sexual behavior was 73.2%.